Influence of personality variables, impulsivity, perfectionism, self-esteem and self-efficacy in Work Craving - Serrano-Fernández, María-José; Boada-Grau, Joan; Assens-Serra, Jordi; Boada-Cuerva, Maria; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2019)
Background: Recent studies have suggested a relationship between certain personality variables and work addiction. In the present work we conduct a predictive study of the background variables of work craving through the variables Impulsivity, Personality, Perfectionism, Self-esteem and Self-efficacy. Method: The participants were 332 workers obtained by non-probability sampling. We used the FACTOR programs (version 7.2) and SPSS 23.0. Results: The predictive capacity of personality variables and self-esteem is determined on the work craving. Conclusions: Work craving can be predicted through certain variables (Emotional Stability, Perfectionism and Self-esteem). This research contributes to greater knowledge of work addiction and to the empowerment of a healthy lifestyle that can be affected by addiction to work. No funding has been received to make this article.